O sistema eleitoral brasileiro à luz de uma teoria crítica do constitucionalismo dirigente - Santos, Thiago Luiz dos (2024)
The Theory of the Governing Constitution advocates for the supremacy of the Constitution over politics and both over the economy, relating closely to the normative force of the Magna Carta. Adapted to countries with differentiated modernity, such as Brazil, it aims to address the condition of sub-citizenship that affects a significant portion of its population by reducing social inequalities and promoting social justice. However, constitutional praxis tends to diverge from the spirit of the Magna Carta due to the forces of constitutional immobility, which delay or even prevent the realization of its principles. Embedded in the Legislative Branch and opposed to the aspirations of marginalized groups, these forces paradoxically succeed in electoral contests, securing the support of those whom they victimize once they attain political power. In light of this, the first chapter seeks to analyze whether the 1988 Brazilian Constitution (CRFB/88) can be classified as a Governing Constitution within the framework of the corresponding Theory; it explores the best aspect of this theory for Brazilian reality, examines whether the implementation of the constitutional project tends toward substantial democracy, and investigates the forces of constitutional immobility. The second chapter aims to examine the election system for the National Congress and presents alternative electoral possibilities by detailing the components of this system and exploring alternatives within each one. It also introduces foundational aspects of the system’s interface with the party system and the Judiciary. Building on these insights, the third chapter critically analyzes, from the perspective of Governing Constitutionalism and through Walter Benjamin’s critical theory, the election system for the Federal Legislature, demonstrating it as a catalyst for the rise of immobility forces and a mechanism for maintaining a permanent state of exception imposed on sub-citizens. The study concludes that the CRFB/88 aligns with the Theory of the Governing Constitution, provided it is adapted to Brazil's differentiated modernity. Furthermore, from the viewpoint of this Theory and Benjaminian critique, the structuring of the electoral system for the Legislature facilitates the rise of immobility forces to political power, fostering the delay — and even stagnation — of its nation-building project and sustaining the marginalized Brazilian segments in a “permanent state of exception.” The research was conducted using a qualitative approach, consulting bibliographic sources and employing Benjamin's sui generis Marxist critical theory as its method